Empowering Leadership in Creativity and Work-Effort: An Elucidation through the Psychological Empowerment and Self- Leadership of the Millennials Generation - Muhammad Ikhsan Alif; Tur Nastiti (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2022)
The purpose of this article is to elucidate the relations of empowering leadership on creativity and work-effort by using psychological empowerment and self-leadership. This elucidation contributes to fill the void in empirical studies by simultaneously examining the dynamics of relations among empowering leadership, creativity, work-effort, psychological empowerment, and self-leadership. The social exchange theory is applied to theoretically explain the psychological mechanisms among the constructs. As millennials are categorized as a creative generation, this study focuses on discussing the factors influencing their creativity and work-effort, with a specific notion of empowerment. This study is based on survey data (n = 113) of millennial generation employees working in digital start-up creative industries in Indonesia. Partial least squares structural equation modeling (PLS-SEM) is used to estimate the model. Results of the study find that empowering leadership influences employee creativity and work-effort either directly or indirectly through psychological empowerment and self-leadership. More specifically, the psychological empowerment of employees partially mediates the influence of empowering leadership on employee creativity and employee work-effort. Employee self-leadership also partially mediates the effect of empowering leadership on psychological empowerment, creativity, and employee work-effort. This study implies the practical and theoretical application of empowering leadership in the creativity context of the millennial generation.